Exploring the Link between Corporate Governance and Financial Information Quality: A Comprehensive Bibliometric Analysis - JAMAL-EDDINE, Kaoutar; CHARBA, Abdelkader (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025, 2025)
The quality of financial information is crucial for establishing a company's transparency and integrity, which, in turn, affects its reputation and ability to attract investors. The effective application of corporate governance is expected to improve the quality of financial reporting by ensuring that financial data accurately reflects a company’s performance and financial position. This paper aims to conduct a bibliometric analysis of corporate governance literature, providing an overview of current trends in publications and their impact on the quality of financial information, using data from the Scopus and Web of Science databases. The analysis employs bibliometric software, VOSviewer, to evaluate various metrics. The study examines a sample of 670 articles published between 2018 and 2024 in the Scopus and Web of Science databases. The findings show a significant upward trend in the volume of corporate governance literature, characterized by increased collaboration among authors. The results of this study, which explores how corporate governance influences financial reporting, will offer valuable insights for researchers, regulators, corporations, and investors.